Cardiovascular risk management in patients with coronary heart disease in primary care: variation across countries and practices : an observational study based on quality indicators - Lieshout, Jan van; Ludt, Sabine (BMC family practice, 2012)
Primary care has an important role in cardiovascular risk management (CVRM) and a minimum size of scale of primary care practices may be needed for efficient delivery of CVRM . We examined CVRM in patients with coronary heart disease (CHD) in primary care and explored the impact of practice size.